A Rare Genetic Syndrome Linked to Oligodontia and Distinct Facial Phenotypes in a Moroccan Boy - Zidane, Fatima Ezzahra; Rouijel, Soukaina; Alloussi, Mustapha El (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
Introduction: Agenesis of teeth is the most prevalent developmental dental anomaly in humans. Various terms are used to describe the congenital absence of teeth, with oligodontia referring to the absence of at least six permanent teeth, excluding the third molars. Oligodontia is a dental condition characterized by the congenital absence of more than six primary or permanent teeth, excluding the wisdom teeth. This hereditary disorder often presents with additional dental abnormalities, such as altered tooth size, conical shape, taurodontism, enamel defects, and delayed eruption. Oligodontia can be isolated or associated with ectodermal dysplasia, a diverse group of rare disorders, as well as other syndromes. Patient Information: This report describes distinct facial phenotypes along with dental features of a six-and-a-half-year-old Moroccan boy with oligodontia, who appears to be in generally good health. Clinical Findings: Three syndromes commonly linked to oligodontia are discussed, with Dubowitz syndrome emerging as the most likely diagnosis based on the patient's facial phenotype. This may represent the first reported case of this nature in Morocco, though further investigation, including genetic analysis, is needed to confirm the diagnosis. Conclusion: Oligodontia can either occur in isolation or in association with ectodermal dysplasia and other syndromes. Early diagnosis is crucial to prevent complications and improve outcomes, making this condition relevant for both medical and dental professionals.